Writings against death : the autobiographies of Simone de Beauvoir - Bainbrigge, Susan (Faux titre, 2005)
Much has been written on Simone de Beauvoir, one of France's leading intellectual figures of the 20th century. The sheer volume of her autobiographical writings testifies to her indefatigable questioning of the nature of existence and her personal and public engagement in the world over the best part of a century. This study aims to re-evaluate her extensive autobiographical œuvre, exploring its place in relation to the French autobiographical canon, and in the light of recent theorisations of autobiography. It presents readings which engage critically with existentialism, feminist theory, and.